Ulcerative Colitis with Henoch Schonlein Purpura in Pediatric Patient: A Case-Report - Ninung Rose Diana Kusumawati; Juwita Pratiwi; Sonya Leonardy Low; Dyan Ajeng Paramitha; Wahyu Aditya Prawirasatra; Nindya Riesmania Pratiwi; Adinda Ratna Puspita (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2023)
Background: Inflammatory bowel disease (IBD) is defined as idiopathic disorder which associated with inflammation of gastrointestinal tract. Ulcerative colitis (UC) and Chron's disease are the predominant forms of IBD. Henoch Schonlein Purpura and UC share some similar symptoms and can mimic each other especially in children. In this case report, we present an eight-year-old boy who had main complaint of recurrent bloody stools and abdominal pain.  Diagnosis was made through history taking, physical examination, laboratory examination and colonoscopy in this patient. Case: A boy aged 8 years and 1 month had main complaint of bloody stools with fluid consistency. This complaint was accompanied by abdominal pain all over the abdominal region and vomiting. Upon physical examination, the child was in pain. The vital signs were within normal limits. Laboratory examination showed leukocytosis. The routine stool examination showed malabsorption of fat, protein, and carbohydrates, followed with positive erythrocytes, leukocytes, epithelium, bacteria, and yeast cells; but the stool culture was sterile. Gastroscopy and colonoscopy were performed which showed erosive gastritis, duodenitis, and proctitis. Discussion: The relationship between ulcerative colitis and HSP remains unknown. Recent research showed overproduction of IgA may induce chronic inflammation in the intestinal. While HSP is IgA/immune complex mediated, IBD is thought to be predominantly T-cell driven. Recently, in IBD patients especially those with ulcerative colitis, IgA were found in their histopathologic biopsy result. Conclusion: The relationship between ulcerative colitis and HSP remains unknown. Recent research has shown that the overproduction of IgA may induce chronic inflammation in the intestinal. As such, symptoms of both diseases may mimic each other as seen in our patients.